Tree-rings in Mediterranean pines - can we ascribe them to calendar years? - Balzano, Angela (Les (Ljubljana), 2019)
A tree ring is defined as a band of xylem-cell layers produced in one year. In Mediterranean trees cambium often produces several bands of alternating early- and latewood during one calendar year, resulting in Intra-Annual Density Fluctuations (IADFs). We present some characteristics of growth layers in Pinus pinea (stone pine) growing on Vesuvius Mountain (near Naples, Italy). The trees showed uninterrupted wood production from January 2015 till the end of January 2016. The ring formed in this period contained five different layers of wood types. Therefore, the wood formed between January and March 2015 would be falsely ascribed to latewood of the tree ring 2014, and the wood formed between March 2015 and the end of January 2016 would be classified as tree ring 2015. We also showed differences in cambium activity in late autumn between years: in November 2015 and 2018 the cambium was still active and not active anymore, respectively. Furthermore, we present the structure of the wood formed in the year 2017 affected by a wildfire in July. Such cases where the growth layer cannot be exactly ascribed to a calendar year should be considered in dendrochronological studies of Pinus pinea and other Mediterranean species.
Keywords: branike; earlywood; gostotna variacija v prirastni plasti; intra-annual density fluctuation; Italija; Italy; kasni les; ksilogeneza; latewood; letnice; pinja; Pinus pinea; rani les; ree ring boundary; traheide; tree ring; xylogenesis